Etika dan Perilaku Koruptif dalam Praktik Manajemen Laba: Studi Hermeneutika - Akhmad Riduwan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2010)
The purpose of this study is to obtain understanding about the opinion and attitude of informants – i.e. accounting educator, management accountant, public accountant, investment advisor, credit analyst, and tax auditor – on earnings management practices performed by managers. This study is motivated by previous studies findings that disclosed a reality that earnings management practices is a facticity in enterprises financial reporting under various motivations and interests. Based on qualitative approach and analysis, particularly interpretive or a hermeneutic approach, the result of this study gives an understanding that informants had different opinion and attitude on earnings management practices.In the accountants’ and tax auditor’s perspective, earnings management practices cannot be viewed as an earnings manipulation as long as that practices are performed in the frame of accounting standards. Accountants also gave the opinion that earnings management practices cannot be viewed as a corruptive behaviour, unless that practices are not performed according to accounting standards. However, in the investment advisors' and credit analysts’ perspectives, earnings management practices performed under any patterns and strategies are the reflection of a corruptive behaviour motivated by corrupted mind. They gave the opinion that earnings management practices are always performed systematically under certain motivation and interest. Earnings management are invaluable practices for enterprise’ stakeholders. Therefore, the practices must be rejected.Keywords: Accrual accounting, earnings management, corruptive behaviour, corrupted mind.